2008
DOI: 10.1128/jvi.02506-07
|View full text |Cite
|
Sign up to set email alerts
|

Rice Yellow Mottle Virus , an RNA Plant Virus, Evolves as Rapidly as Most RNA Animal Viruses

Abstract: The rate of evolution of an RNA plant virus has never been estimated using temporally spaced sequence data, by contrast to the information available on an increasing range of animal viruses. Accordingly, the evolution rate of Rice yellow mottle virus (RYMV) was calculated from sequences of the coat protein gene of isolates collected from rice over a 40-year period in different parts of Africa. The evolution rate of RYMV was estimated by pairwise distance linear regression on five phylogeographically defined gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 37 publications
2
36
0
Order By: Relevance
“…In California, nucleotide diversity of Cucumber mosaic virus, CTV, and Citrus psorosis virus have been estimated as ≈0. 030 (31,34,46), which is also low in comparison with bacteriophages, animal viruses, and some plant viruses (14,20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In California, nucleotide diversity of Cucumber mosaic virus, CTV, and Citrus psorosis virus have been estimated as ≈0. 030 (31,34,46), which is also low in comparison with bacteriophages, animal viruses, and some plant viruses (14,20).…”
Section: Resultsmentioning
confidence: 99%
“…In California, nucleotide diversity of Cucumber mosaic virus, CTV, and Citrus psorosis virus have been estimated as ≈0. 030 (31,34,46), which is also low in comparison with bacteriophages, animal viruses, and some plant viruses (14,20).Genetic differentiation was evaluated with the statistical tests Ks*, Z*, and S nn , and the extent of genetic differentiation and, therefore, gene flow was estimated with the coefficient F st . When samples collected from the USDA Germplasm collection (located at UC Davis) were compared with the isolates collected from commercial fields in California, the F st value was equal to -0.021 and the three statistical tests were nonsignificant.…”
mentioning
confidence: 99%
“…species of the Luteoviridae), 9000 years ago; potyviruses, 6600 years ago; sobemoviruses, 3000 years ago; and the TYLCVs, which are probably representative of the begomoviruses, 10 000 years ago. Thus, these major taxa of crop-infecting viruses all diversified in the period since humankind invented agriculture (Fargette et al, 2008b;Gibbs et al, 2008c) although, of course, they may have originated even earlier and survived as small founder populations. This raises the question as to whether the invention and spread of agriculture itself triggered and fostered their radiation and dominance.…”
Section: Viral Origins Evolution and The Invention Of Agriculturementioning
confidence: 99%
“…In the case of plant RNA viruses, it has been repeatedly reported that their populations are highly genetically stable (Rodríguez-Cerezo et al 1991;Fraile et al 1997;Marco and Aranda 2005;Herránz et al 2008) in comparison with their animal counterparts, although reports of higher substitution rates also exist (Fargette et al 2008;Gibbs et al 2008). This peculiar behavior might be due in part to stronger stabilizing selection, weaker immune-mediated positive selection (García-Arenal et al 2001), the existence of strong bottlenecks during cell-to-cell movement and systemic colonization of distal tissues (Hall et al 2001;Sacristán et al 2003;Li and Roossinck 2004), severe bottlenecks during vector-mediated transmission (Ali et al 2006;Moury et al 2007;Betancourt et al 2008), or differences in the replication mode compared to lytic animal viruses (French and Stenger 2003;Sardanyés et al 2009).…”
mentioning
confidence: 99%